1996
DOI: 10.1021/jo961526y
|View full text |Cite
|
Sign up to set email alerts
|

Chair/Twist-Boat Energy Gap in Monocyclic, Conformationally Unconstrained Polyalkylcyclohexanes

Abstract: A conformational search procedure (HUNTER), in combination with the MM3(92) program, was used for the exploration of the conformational hypersurface of alkyl-substituted cyclohexanes and for the calculation of their chair/twist-boat (TB) energy gap. The systems studied were conformationally unconstrained polyalkylcyclohexanes (alkyl = methyl, ethyl, isopropyl, and tert-butyl) possessing either geminal and/or vicinal arrangements of the alkyl groups, but differing in the number of alkyl substituents and in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…The presence of different conformers of the molecule of cyclohexane in gas phase is possible due to chair-chair inversion of the ring (Figure 1). According to dynamical DFT calculations of Ionescu et al [37] this process undergoes through two half-chair (or sofa) and one t-boat conformations, with energy barrier of 41.4 kJ mol À1 (9.9 kcal mol À1 ), which is in agreement with experimental data. [38] The main objective of this work is to study the adsorption mechanisms of cyclohexane in numerous zeolitic frameworks with the final aim of finding a relation between the host structures and the preferential configuration adopted by the molecules.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The presence of different conformers of the molecule of cyclohexane in gas phase is possible due to chair-chair inversion of the ring (Figure 1). According to dynamical DFT calculations of Ionescu et al [37] this process undergoes through two half-chair (or sofa) and one t-boat conformations, with energy barrier of 41.4 kJ mol À1 (9.9 kcal mol À1 ), which is in agreement with experimental data. [38] The main objective of this work is to study the adsorption mechanisms of cyclohexane in numerous zeolitic frameworks with the final aim of finding a relation between the host structures and the preferential configuration adopted by the molecules.…”
Section: Introductionsupporting
confidence: 79%
“…The lowest energy conformation of cyclohexane is chair form, but this molecule also exhibits local energy minima for twisted boat (t‐boat) conformation . The difference between enthalpies of conformations of the molecule of cyclohexane is presented in Figure ,,. Considering only chair and t‐boat conformers, Boltzmann distribution indicates that for gaseous cyclohexane at 298 K only ca 0.01 % of the molecules remain in the t‐boat conformation.…”
Section: Introductionmentioning
confidence: 99%
“…17m y -␤-caryophyllene 36 molecules , an investigation of the chairrtwist energy gap in polyalkyl-Ž . 40 WEISER, HOLTHAUSEN, AND FITJER manuscript. This work was supported by the Fonds der Chemischen Industrie and the Niedersachsen Fund.…”
Section: Discussionmentioning
confidence: 96%
“…10 A systematic MM3 study revealed that the minimal steric requirements for the relative stabilization of the twist conformation of cyclohexane are two methyls and two isopropyl groups arranged in either a cis-trans-trans-1,2,3,4-or all-cis-1,2,4,5-substitution pattern. 19 In principle, if the steric destabilization ensuing from the presence of a bulky axial substituent in a tetrahydroxycalix[4]arene is sufficiently large, it could be expected that the intrinsic conformation preferences of the calix skeleton for the cone conformation may be altered. However, analysis of the NMR spectra of the trans alkyl-substituted derivatives 7a-d indicated that, in all cases, the preferred conformation is still the cone.…”
Section: Axial Substituents In the Cone Form Of The Trans Derivativesmentioning
confidence: 99%